Customer satisfaction and awareness towards Islamic Banking products in Malaysia / Mardhiah Md Junos - Md Junos, Mardhiah (Academy of Contemporary Islamic Studies (ACIS), 2017)
The Islamic banking system is gaining improvement day by day. In Malaysia, the Islamic banks have to compete with the conventional banks that has longer history than Islamic banks. Nowadays, we can see many international conventional banks have started to open branches which operate in accordance with the Islamic Shariah principles which lead to the competition between the Islamic banks that offer the same products and services. For this competition, Islamic banks should know how to face strong competition. In this study, an attempt is made to access the level of satisfaction and awareness of customers towards Islamic banking. In addition, this study also aims to examine the perceptions of customers towards Islamic banking. The methods used in this research are mixed method which is qualitative like library research and participant observation. Whereas, quantitative methods consists of conducting survey. The survey shows the totals of 20 respondents from different demographic profiles are selected for the purpose of this study. The result shows that majority of the respondents are aware of Islamic banking in Malaysia but some of them do not aware of the Islamic banking products and services. The perceptions of customers towards the Islamic banks are varied among themselves. The recommendations suggested in this research in order to enhance the Islamic banking are Islamic banks need to implement viable service and programs. The failure to provide the right quality of service, implement the training programs among their staff which can be useful tools for improving the managerial capabilities Islamic banks staff and the last is recommended methods in conducting the survey for the next research are questionnaires and interviews in terms of the bank criteria selection.